Penurunan Fosfat dan Kimia Organik dengan menggunakan Modifikasi Parit Oksidasi secara Pararel - Novembrianto, Rizka; Nisa', Syadzadhiya Qotrunada Zakiyayasin; Munawar, Munawar; Rhomadhoni, Muslikha Nourma (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2024)
Laundry business activities produce waste water from the washing process and have the potential to pollute water bodies. The number of domestic laundry activities is currently experiencing significant growth, as these activities increase, the amount of waste water released is also increasing. So far, the waste water produced has been directly discharged into the environment. Initial testing of the sample showed that the results did not meet the threshold according to East Java Governor Regulation No. 72 of 2013, so it is necessary to treat waste water effectively. In this research, laundry wastewater was treated using an oxidation ditch. The multilevel modified Parit Oksidasi is made from an activated sludge unit. Seeding and acclimatization takes 14 days to obtain optimum processing. The best variation uses 3 wavemaker units to reduce COD by 91.87%, phosphate by 98.49% and TDS by 57.21%. Apart from that, other contents in the sludge were also identified, namely oxygen (44.28%), carbon (21.25%), sodium (9.73%), calcium (7.11%), silica ( 4.46%), Sulfide (4.36%), Magnesium (2.73%), Chlorine (2.68%), Potassium (1.59%), Iron (0.61) and Phosphorus (0.07 %).